Preparation and Characterization of Prednisolone Acetate Microemulsion for Ophthalmic Use - Al-Rubaye, Reem A. Alfaris; Al-Kinani, Khalid K. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Prednisolone acetate is an ester form of prednisolone, used topically as an ophthalmic suspension to treat many inflammatory ocular conditions, where its absorption from suspension is highly variable and has poor dose accuracy.Objectives: The main aim of this research is to formulate and evaluate prednisolone acetate microemulsion for ophthalmic use to increase solubility, residence time, and corneal permeability of the drug to enhance patient compliance and treatment efficacy.Methods: Twenty-four prednisolone acetate-loaded microemulsion (0.5%w/w)  formulas were prepared using oleic acid, isopropyl myristate as (oil phase) (1:1), tween 80, labrasol, and cremophor EL as (surfactant), ethanol, polyethylene glycol 400, propylene glycol, transcutol P as co-surfactant and Sörensen isotonic phosphate buffer saline pH 7.4 as the aqueous phase at different Smix ratios (1:1), (1:2) and (2:1) by aqueous titration method to construct pseudoternary phase diagram to determine the existence of microemulsion region. All the prepared formulas were subjected to different evaluation tests to determine the optimum formula.Results:  observations of the microemulsion showed that it had a clear and transparent yellowish color, formulation F9 composed of oleic acid and isopropyl myristate in a ratio (1:1) as oil, tween 80(80TW) as a surfactant, and propylene glycol: ethanol (1:1) in a ratio (2:1) as cosurfactant gave the best particle size (10.18nm), polydispersity index (0.2216), zeta potential (-25,91), % of transmittance (99.382%±0. 09), and drug content (100±0.16). Microemulsions formulation provided considerably higher permeability than the marketed eye-drop suspension (Optipred®) and improved bioavailability.Conclusions:  The research results suggest that microemulsion-containing prednisolone acetate is a promising ocular carrier for the controlled release of prednisolone acetate in treating anterior segment inflammation.